FACTORS PREDICTING SELF-MANAGEMENT BEHAVIORS AMONG PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE 3 IN SUPHANBURI PROVINCE, THAILAND - Yoomuang, Prin; Suphannakul, Pattama (Malaysian Journal of Public Health Medicine, 2023)
This research examined factors predicting self-management behaviors of patients with chronic kidney disease (CKD) stage 3 in Suphanburi Province. A multi-stage sampling technique was used to recruit participants from 10 hospitals in 10 districts of Suphanburi Province. A total of 228 participants have been diagnosed with CKD stage 3. Data were collected using a questionnaire with an overall Cronbach’s alpha coefficient of 0.96. Data were analyzed using descriptive statistics and stepwise multiple regression at the significant level of 0.05. The results showed that the social support scores from medical personnel had high levels (52.20%). Meanwhile, the score of healthcare providers, village health volunteers, and families had low levels (76.80%, 98.20%, and 85.10%, respectively). For illness perception, perceived benefits, self-efficacy, and self-management behaviors of patients with CKD stage had high levels (62.30%, 92.10%, 95.60%, and 50.90%, respectively). Meanwhile, CKD knowledge had moderate levels of 58.30%. The strongest predictor of self-management behaviors in a patient with CKD stage 3 was social support from healthcare providers (Beta = 0.348, p-value < 0.001), followed by perceived benefits (Beta = 0.299, p-value < 0.001) and self-efficacy (Beta = 0.266, p-value < 0.001), respectively. These factors account for 42.70% of predicting self-management behaviors of a patient with CKD stage 3. In conclusion, healthcare providers should encourage the self-management behaviors of patients with stage 3 CKD by enhancing their perceived benefits and self-efficacy to modify behaviors in order to slow the progression of CKD.